Clinical Practice Guidelines - Unger, Thomas (2020)
The ISH Guidelines Committee extracted evidence-based content presented in recently published extensively reviewed guidelines and tailored and standards of care in a practical format that is easy-to-use particularly in low, but also in high resource settings – by clinicians, but also nurses and community health workers, as appropriate. Although distinction between low and high resource settings often refers to high (HIC) and low- and middle-income coun tries (LMIC), it is well established that in HIC there are areas with low resource settings, and vice versa. Herein optimal care refers to evidence-based standard of care articulated in recent guidelines1,2 and summarized here, whereas standards recognize that standards would not always be possible. Hence essential stan dards refer to minimum standards of care. To allow specifica tion of essential standards of care for low resource settings, the Committee was often confronted with the limitation or absence in clinical evidence, and thus applied expert opinion